Pharmacokinetics of ceftriaxone following single ascending intravenous doses in sheep - Corum, Duygu Durna; Corum, Orhan; Altan, Feray; Eser Faki, Hatice; Bahcivan, Emre; Er, Ayse; Uney, Kamil (Elsevier BV, 2018)
Abstract The objective of this study was to evaluate the pharmacokinetics of CTX following intravenous administration of ascending doses in sheep. In this study, six clinically healthy Akkaraman sheep (2.4 ± 0.4 years and 50 ± 3 kg of body weight) were used. CTX was administered intravenously to each sheep at 20, 40, and 80 mg/kg doses in a crossover design with a 15-day washout period. Plasma concentrations of CTX were measured using the high-performance liquid chromatography-UV method. Pharmacokinetic parameters were calculated by non-compartmental analysis. CTX was well tolerated following administration at 20, 40, and 80 mg/kg doses. The elimination half-life following administration of 40 and 80 mg/kg doses were significantly longer than that of 20 mg/kg dose (P   0.05). When compared to 20 mg/kg, dose-normalized AUC0–∞ at the 80 mg/kg dose significantly increased (P   minimum inhibitory concentration (MIC) of >40% for the treatment of infections caused by bacteria with MIC values ≤2, ≤4, and ≤16 μg/mL, respectively. This information may be helpful in adjusting the dosage regimen, but there is a need for future work.
Keywords: Sheep; Ceftriaxone; Pharmacokinetics; Ascending Dose; Ascending dose; 3. Good health